2019
DOI: 10.1007/s11071-019-05130-2
|View full text |Cite
|
Sign up to set email alerts
|

Reset control approximates complex order transfer functions

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Because of the phase lead provided by CR CgLp, it is expected that CgLp+PI n D show a lower overshoot as compared to PI n D. While this expectation holds, for reset control systems, PM is not the only parameter affecting the transient response. In CR CgLp controllers, ω l also significantly affects the transient response, since as discussed in (9), the resetting condition in closed-loop changes. The effect of presence of CR CgLp and variation ω l on the step response of the CR CgLp+PID control system has been simulated in Simulink environment of Matlab and presented Fig.…”
Section: Closed-loop Transient Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the phase lead provided by CR CgLp, it is expected that CgLp+PI n D show a lower overshoot as compared to PI n D. While this expectation holds, for reset control systems, PM is not the only parameter affecting the transient response. In CR CgLp controllers, ω l also significantly affects the transient response, since as discussed in (9), the resetting condition in closed-loop changes. The effect of presence of CR CgLp and variation ω l on the step response of the CR CgLp+PID control system has been simulated in Simulink environment of Matlab and presented Fig.…”
Section: Closed-loop Transient Responsementioning
confidence: 99%
“…In order to address the drawbacks and exploiting the benefits, the idea was later extended to more sophisticated elements such as "First-Order Reset Element" [4], [5] and "Second-Order Reset Element" [6] or using Clegg's integrator in form of PI+CI [7] or resetting the state to a fraction of its current value, known as partial resetting [8]. Reset control has also recently been used to approximate the complex-order filters [9], [10]. Advantage of using reset control over linear control has been shown in many studies especially in precision motion control [8], [11]- [15], [15]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…In almost all of the reset elements studied in the literature, all of the coupled states of the reset element reset [7,18,19]. In other words, there is no coupling between a reset and a non-reset state in the architecture of a reset element.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional-order derivatives and integrals have been used for control designs like Fractional PID [21][22][23][24] or CRONE control [25][26][27]. Recently, fractionalorder elements have also been used within reset elements [19,[28][29][30] in order to approximate complexorder behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…This means that introducing non-linear reset control favours the freedom of design and improves the stability margins. Recent research on reset control can be found in [3]- [8].…”
Section: Introductionmentioning
confidence: 99%